Gold Decorated Graphene by Laser Ablation for Efficient Electrocatalytic Oxidation of Methanol and Ethanol. Issue 8 (16th July 2014) - Kumar, V. Lakshman; Siddhardha, R. S. Sai; Kaniyoor, Adarsh; Podila, Ramakrishna; Molli, Muralikrishna; Kumar, Sai Muthu; Venkataramaniah, K.; Ramaprabhu, S.; Rao, A. M.; Ramamurthy, Sai Sathish
Abstract A well‐known limitation in the fabrication of metal‐graphene composite has been the use of surfactants that strongly adsorb on the surface and reduce the performance of the catalyst. We demonstrate here a novel one‐pot synthesis of gold nanoparticles by laser ablation of gold strip and in‐situ decoration on graphene substrate. Not only the impregnation of nanoparticles was linker free, but also the synthesis by itself was surfactant‐free. The composite materials were well characterized morphologically and functionally using electron microscopy, X‐ray and electron diffraction, Raman spectroscopy, Zeta potential, electrochemical measurements and UV‐Visible spectroscopic techniques. This linker‐free gold‐graphene based composite has been employed for catalytic applications pertaining to electrooxidation. We have explored the use of this composite as a binder‐free electrode in electrocatalytic oxidation of methanol and ethanol in alkaline medium. Additionally, the onset potential for ethanol oxidation was found to be more negative, −100 mV, an indication of its promising application in direct ethanol fuel cells.